Mission or money? Trends in scholarly publishing since c.1850 - Fyfe, Aileen (Septentrio Conference Series, 2019)
Watch the VIDEO. Keynote presentation. The current debates about the future of academic publishing have generated much discussion about the most appropriate way to support financially the widespread circulation of knowledge. Yet there have been debates about this since at least the 1890s. Drawing upon my historical research, I will describe how scholarly publishing has a long history of not making money. Indeed, until the mid-twentieth century, its costs were frequently sponsored (i.e. subsidised) by learned societies, by universities, by government and by private donors. It was only in the early Cold War years, in a time of expanding output of research, that mission-driven publishers began to seriously focus on sales income as a means of covering costs; and then, later, as a means of generating income. Should publishing be treated as mission, or as a means to mission? My talk will seek to untangle the historical relationship between publishing, money-making and scholarly mission.